Contributive Factors of Tolerance among Senior High School Students - Septian, Muhammad Rezza; Supriatna, Mamat; Nurihsan, Juntika; Budiman, Nandang (Jurnal Kajian Bimbingan dan Konseling, 2023)
This article aims to explore the contributing factors of tolerance in senior high school students. This research covers the concept of tolerance theory and aspects that contribute to tolerance. The study was carried out using a cross-sectional survey method with a quantitative approach. The population in this study were high school students in the city of Bandung, Indonesia. The research sample was taken using a random sampling technique. The research sample consisted of 300 high school, vocational high school, and Madrasah Aliyah students in the city of Bandung. Data collection was completed using tolerance instruments, and data analysis used confirmatory factor analysis (CFA). The results of this study indicate that the greatest contributing aspect to the tolerance of senior high school students in Bandung was the aspect of peace. Meanwhile, the lowest contribution was observed in the aspect of equality. The peace aspect consists of indicators of caring, fearlessness, and love. The results of this study can be used as material and consideration for further research to develop a model or program of guidance and counseling services empirically designed to develop tolerance.